The role of interactive sports programs on Algerian television in developing sports culture among students of media and sports communication - Merichiche , khaled; djellal , salah eddine (sports creativity, 2025)
The article deals with the role of interactive sports programs on Algerian television in developing sports culture among students of media and sports communication, as sports media is one of the most important means of education and sports education, as it seeks to develop all of the knowledge, perceptions and information of the audience of viewers, Where we adopted the comprehensive survey of the study community consisting of 55 students, and the results showed that interactive sports programs on Algerian TV contribute to increasing students' knowledge of sports in terms of laws, values, knowledge and analytical capabilities of sporting events.